pH-responsive hydrogel system loaded with curcumin-preconditioned mesenchymal stem cell exosomes for enhanced diabetic wound healing in orthopedic applications - Li, Senlei; Li, Yangyang; Chen, Yazhou; Guo, Jiawen; Zou, Qian; Ding, Qiuyue (Frontiers in Bioengineering and Biotechnology, 2025)
Wounds, a major complication in orthopedic-related diseases, present significant challenges for orthopedic surgeons due to impaired healing driven by vascular dysfunction, oxidative stress, and chronic inflammation. This study introduces an injectable, self-healing, pH-responsive hydrogel system delivering curcumin-preconditioned mesenchymal stem cell (MSC)-derived exosomes (Cur-Exos) to enhance diabetic wound repair, offering a cell-free therapeutic strategy with applications in orthopedic regenerative medicine. The hydrogel, formed through dynamic cross-linking of amphoteric chitosan and multi-armed polyethylene glycol, exhibits antibacterial properties and degrades selectively in the acidic microenvironment (pH 4.5–6.5) of diabetic wounds. Loaded with Cur-Exos, it enables controlled release of bioactive molecules, leveraging the enhanced antioxidant, anti-inflammatory, and pro-angiogenic properties of exosomes from curcumin-preconditioned MSCs. In vitro, Cur-Exo@Gel exhibited excellent biocompatibility, promoted endothelial cell migration, and enhanced angiogenesis, while reducing oxidative stress. It also modulated macrophage polarization by decreasing pro-inflammatory M1 markers (iNOS) via the upregulation of Iκβ-α and reduced p65 phosphorylation, fostering an anti-inflammatory microenvironment. The hydrogel’s inherent antibacterial properties (>50% reduction in Escherichia coli and Staphylococcus aureus, p < 0.05) further mitigate infection risks that are critical in orthopedic wounds. In vivo, in a diabetic rat full-thickness skin defect model, Cur-Exo@Gel significantly reduced wound areas, with enhanced epithelial migration and collagen deposition. These findings highlight Cur-Exo@Gel as a promising cell-free therapeutic strategy for accelerating chronic orthopedic wound repair, offering novel insights for regenerative orthopedics.